3D structural control and spatial distribution of Zn-Pb-Cu grades in the Palmeirópolis VMS deposit, Brazil. Issue 2 (3rd April 2022) - de Oliveira, Saulo B.; Torresi, Ignacio; Rossi, Debora A. L.
ABSTRACT: The Palmeirópolis Zn-Pb-Cu volcanogenic massive sulfide deposit consists of four areas, presenting distinct features regarding host rocks, the geometry of ore bodies, hydrothermal alteration, deformation intensity, and metal proportions. The seven modeled Zn-Pb-Cu ore bodies occur mainly along with the contact between the Mesoproterozoic acid and basic metavolcanics within amphibolite facies. Some characteristics such as the relation of higher Zn-Pb and Cu grades to a higher proportion of acid and basic metavolcanic host rocks respectively, the same metamorphic grade and the gradational contact between volcanic host rocks, and distribution of alteration halo suggest that the original stratigraphy is still preserved. A smooth folding superposing the initial tight folds that define the ore bodies indicates at least two deformation events after the Zn-Pb-Cu mineralisation in the Palmeirópolis deposit. Finally, the geometry of the 3D ore bodies in Palmeirópolis are discussed against other VMS deposits around the world with 3D data available in terms of age, metamorphic, and deformation grades.